Pelatihan Fortifikasi Daging Ikan Sebagai Sumber Protein Nugget Ubikayu di Desa Tambusai Batangdui - Suparmi; Syafrani; Sumarto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Effort to increase public knowledge of appropriate technology is to produce a product that is useful to support their welfare. One of them is the technology of fisheries and agricultural utilization. The potential of fisheries and agriculture is sufficiently developed in Riau, therefore, it is necessary to make efforts so that the harvest from fish and cassava farmers has economic value which is to increase the added value from its harvest, become a diversified product. The solution offered to partners is the application of appropriate science and technology in training technology of fish meat utilization for protein fortification in cassava nuggets, a quality product and safe for consumption, and as an effort to develop partner empowerment especially PKK cadres. The method of approach taken was in quality guidance to partners as micro-entrepreneurs and as an alternative effort to improve family welfare. Besides providing information about management and tips towards sustainable self-sufficiency business, and helping partners in collaborating with the marketing partners of the products produced. In carrying out the activities of participants of the active participation was both during the implementation and post activities, i.e. participants receive well the science and technology provided by universities to improve partner businesses. The ouput of this activity was the skill of PKK cadres in processing cassava into best quality nuggets, which can be used as supplementary food for children as well as opening opportunities as their side livelihood, in the context of business development and increasing family income.